2017
DOI: 10.1021/acs.accounts.6b00617
|View full text |Cite
|
Sign up to set email alerts
|

Confined Water: Structure, Dynamics, and Thermodynamics

Abstract: Understanding the properties of strongly confined water is important for a variety of applications such as fast flow and desalination devices, voltage generation, flow sensing, and nanofluidics. Confined water also plays an important role in many biological processes such as flow through ion channels. Water in the bulk exhibits many unusual properties that arise primarily from the presence of a network of hydrogen bonds. Strong confinement in structures such as carbon nanotubes (CNTs) substantially modifies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
182
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(192 citation statements)
references
References 57 publications
9
182
1
Order By: Relevance
“…Understanding the mechanisms of phase transitions in confined water is one of open problems in condensed matter physics, which stimulates performance of numerous experimental, numerical and theoretical studies [1][2][3][4][5][6][7][8] . So, investigations of the properties of water in a confinement attract the special attention of scientists because of its importance for understanding many biological and geological processes, such as the microscopic processes in membranes and cells; transport processes in pores; capillary phenomena; dynamic processes in the depths of satellites of some planets of the Solar system 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms of phase transitions in confined water is one of open problems in condensed matter physics, which stimulates performance of numerous experimental, numerical and theoretical studies [1][2][3][4][5][6][7][8] . So, investigations of the properties of water in a confinement attract the special attention of scientists because of its importance for understanding many biological and geological processes, such as the microscopic processes in membranes and cells; transport processes in pores; capillary phenomena; dynamic processes in the depths of satellites of some planets of the Solar system 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The size and dimensionality of the cavity as well as the structure, hydrophobicity and roughness of its inner surface all affect the structure and dynamics of the confined water. [6][7][8][9][10][11][12][13][14][15][16] However, in the deeply supercooled regime, experimental results have shown that the dynamics of confined water is rather universal, irrespective of whether the water is located in a solid porous material, hydrating a biomolecule or in a solution below or close to the glass transition temperature, T g , of the entire system. 17 In this paper we will mainly discuss results obtained from differential scanning calorimetry (DSC), dielectric spectroscopy, quasielastic neutron scattering (QENS) and relaxation nuclear magnetic resonance (NMR) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of water molecules in nano‐sized confinement has drawn intensive research interest . Very little research concerning the dynamic behavior of the water wire within precise hydrophilic confinement has been reported.…”
Section: Resultsmentioning
confidence: 99%